Reanalysis of LIGO black-hole coalescences with alternative prior assumptions. Issue Volume 13:Issue S338(2017) (29th January 2019) - Gerosa, Davide; Vitale, Salvatore; Haster, Carl-Johan; Chatziioannou, Katerina; Zimmerman, Aaron
Abstract: We present a critical reanalysis of the black-hole binary coalescences detected during LIGO's first observing run under different Bayesian prior assumptions. We summarize the main findings of Vitale et al. (2017) and show additional marginalized posterior distributions for some of the binaries' intrinsic parameters. These findings were presented at IAU Symposium 338, held on October 16-19, 2017 in Baton Rouge, LA, USA.